Adenosine Triphosphate Release and P2 Receptor Signaling in Piezo1 Channel-Dependent Mechanoregulation - Wei, Linyu; Mousawi, Fatema; Li, Dongliang; Roger, Sébastien; Li, Jing; Yang, Xuebin; Jiang, Lin-Hua (Frontiers in Pharmacology, 2019)
Organs and tissues and their constituent cells are physiologically submitted to diverse types of mechanical forces or stress, one common sequence of which is release of intracellular ATP into extracellular space. Extracellular ATP is a well-established autocrine or paracrine signalling molecule that regulates multiple cell functions and mediates cell-to-cell communications via activating the purinergic P2 receptors, more specifically, ligand-gated ion channel P2X receptors and some of the G-protein-coupled P2Y receptors. The molecular mechanisms that sense mechanical and transduce forces to trigger ATP release are poorly understood. The Piezo1, a newly-identified mechanosensing ion channel, shows widespread expression and confers mechanosensitivity in many different types of cells. In this mini-review, we briefly introduce the Piezo1 channel and discuss the evidence that supports its important role in the mechanoregulation of diverse cell functions and, more specifically, critical engagement of ATP release and subsequent P2 receptor activation in Piezo1 channel-dependent mechanoregulation. Such ATP release-mediated coupling of the Piezo1 channel and P2 receptors may serve a signalling mechanism that is more common than we currently understand in transducing mechanical information to regulation of the attendant cell functions in various organs and tissues.